2013
DOI: 10.1063/1.4799591
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature magnetoelectric coupling in single-phase BaTiO3-BiFeO3 system

Abstract: In this paper, single-phase multiferroic ceramics of (1 − x) BaTiO3 − x BiFeO3 (BT − x BFO) were synthesized by solid-solution method in the wide range of material composition (x = 0.025 – 1.0). The changes in crystal structure were confirmed via X-ray diffractions (XRD) and atomic pair distribution functions (PDFs). The room-temperature ME coupling was found to exhibit significant magnitude in the narrow composition window (x = 0.71 – 0.8) where the average crystal structure was found to be rhombohedral. Espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 30 publications
2
57
2
2
Order By: Relevance
“…[1][2][3] It different functional properties and cross coupled ferroic order parameters make it a potential candidate for nonvolatile memory elements, optical memory devices, abovebandgap photovoltaic devices, micro/nano electromechanical systems, magnetic field sensors, etc. [4][5][6][7][8][9][10] The optical properties of BiFeO 3 (BFO) are also different from most of the perovskite ferroelectric due to its lower bandgap (2.6-2.9 eV) and conducting domain walls. 11,12 Clark and Robertson 13 predicted both direct and indirect bandgaps around 2.5 eV using band structure model, and afterward Ihlefeld et al 14 reported a direct-gap transition at 2.74 eV; however, recently we also found a direct bandgap of 2.55 eV at T ¼ 295 K, an indirect band edge at 2.67 eV.…”
mentioning
confidence: 99%
“…[1][2][3] It different functional properties and cross coupled ferroic order parameters make it a potential candidate for nonvolatile memory elements, optical memory devices, abovebandgap photovoltaic devices, micro/nano electromechanical systems, magnetic field sensors, etc. [4][5][6][7][8][9][10] The optical properties of BiFeO 3 (BFO) are also different from most of the perovskite ferroelectric due to its lower bandgap (2.6-2.9 eV) and conducting domain walls. 11,12 Clark and Robertson 13 predicted both direct and indirect bandgaps around 2.5 eV using band structure model, and afterward Ihlefeld et al 14 reported a direct-gap transition at 2.74 eV; however, recently we also found a direct bandgap of 2.55 eV at T ¼ 295 K, an indirect band edge at 2.67 eV.…”
mentioning
confidence: 99%
“…31 The observed value of ME coupling coefficient in our samples is significantly larger than the reported value of 7 mV/cm Oe for single phase bulk BiFeO 3 sample and 124 mV/cm Oe for 0.9 BFO -0.1 BTO ceramic composite thin films and bulk samples. [33][34][35][36] Such substantially high magnetoelectric coupling coefficient values obtained at room temperature paves the way to fabricate new type of electric-field controlled magnetic random access memory (MERAM), magnetoelectric sensors, voltage tunable RF/microwave signal processing devices, and spintronic devices…”
mentioning
confidence: 99%
“…As reported in Refs. [5,6, and references therein], rhombohedral symmetry is maintained for x = 0-0.3, after which cubic symmetry predominates up to x = 0.93. For x > 0.93 and for a pure BaTiO 3 compound, the structure is tetragonal.…”
Section: Resultsmentioning
confidence: 99%
“…This may be achieved, for example, by structural modifi cations or deformations introduced by cation substitution or doping [5]. Therefore, a solid solution of BiFeO 3 [6].…”
Section: Introductionmentioning
confidence: 99%